TGF-β1 inhibitor enhances the therapeutic effect of microwave ablation on hepatocellular carcinoma - Shufang Xiang; Juan Li; Mei Zhang (International Journal of Hyperthermia)
Background Microwave ablation (MWA) is a widely adopted treatment technique for hepatocellular carcinoma (HCC). However, MWA alone is of limited use and has a high recurrence rate. Transforming growth factor-β1 (TGF-β1) is recognized as a potential therapeutic target for HCC patients. Therefore, this study was designed to investigate whether the TGF-β1 inhibitor could increase the efficacy of MWA therapy for HCC treatment.Methods In vitro, HCC cells challenged with TGF-β1 inhibitor (SB-525334), or normal saline were then heated by microwave. Methyl tetrazolium assays were performed to detect cell survival rate and half-maximal drug inhibitory concentration (IC50). Cell viability and apoptosis were detected by cell counting kit-8 assays, flow cytometry and western blotting. In vivo, the mice injected with HepG2 cells received oral gavage of SB-525334 (20 mg/kg) or normal saline and MWA at a power of 15 W. Tumor volume was recorded. Expression of Ki67 and apoptosis-related proteins were detected by immunohistochemistry and western blotting. TUNEL assays were used to detect cell death ratio. Histopathological changes were examined by hematoxylin and eosin staining. The mechanisms associated with the function of MWA combined with TGF-β1 inhibitor in HCC development were explored by western blotting.Results Combination of MWA and SB-525334 decreased the survival rate and promoted the apoptosis of HCC cells compared with MWA alone. SB-525334 enhanced the suppressive effect of MWA on tumor growth and amplified cell apoptosis. Mechanistically, MWA collaborated with SB-525334 inhibitor inactivated the TGF-β1/Smad2/Smad3 pathway.Conclusion TGF-β1 inhibitor enhances the therapeutic effect of MWA on HCC.